UPAYA MENINGKATKAN KREATIVITAS SISWA DALAM PEMBELAJARAN MATEMATIKA MELALUI MODEL PEMBELAJARAN PAIR CHECKS - Samosir, Benny Sofyan; Novitasari, Wiwik; Sahara, Nur; Sagita, Feny (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
In the current COVID-19 condition, which requires that learning be carried out by e-learning, students' creativity in learning mathematics is getting lower. To overcome this problem, this study applied the Pair Checks learning model. The objectives of the increase in students' mathematical creativity taught by the application of the Pair Checks learning model, to know the increase in student activity taught by the application of the Pair Checks learning model, to know the improvement of teacher performance in learning mathematics through the Pair Checks learning model. This type of research is Classroom Research. Where the research subjects are students of class X MIA 1 SMA Negeri 6 Padangsidimpuan for the academic year, 2020/2021, totaling 21 students. Data collection techniques and tools are tests and observations. The analytical technique used is descriptive. The results of this study after using the Pair Checks learning model that is seen from the results of the students' mathematics learning creativity test increased with the percentage gain in the first cycle from 61.9% to 90.48% in the second cycle, and the total percentage increased by 28.58%. Student activity in learning increased, this is evidenced by the acquisition of a percentage of 70.47% in the first cycle and 93.9% in the second cycle with an increase of 24.43%. The ability of teachers to manage learning has increased, this is evidenced by the percentage gain of 72% in the first cycle and 96% in the second cycle with an increase of 24%. So the results of this study show that the Pair Checks learning model can increase students' creativity in learning mathematics, student activities in class X MIA 1 SMA Negeri 6 Padangsidimpuan.